2022
DOI: 10.1002/cl2.1249
|View full text |Cite
|
Sign up to set email alerts
|

PROTOCOL: Mental disorder, psychological problems and terrorist behaviour: A systematic review

Abstract: This is the protocol for a Campbell systematic review. The objectives are as follows:the first objective of the review (Objective 1-Prevalence) is to present a synthesis of the reported prevalence rates of mental health difficulties in terrorist samples.Where sufficient data is available, the synthesis will be sensitive to the heterogeneity of the terrorism phenomenon by exploring the rates of mental health difficulties for different forms of terrorism and for different terrorist roles (e.g., bombing, logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 81 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…On reviewing the eligible studies, and noting the considerable heterogeneity in all analyses, we considered potential moderators that might explain, in part at least, the evident heterogeneity. Both moderators were anticipated a priori (see Sarma et al, 2022). The first was data source.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On reviewing the eligible studies, and noting the considerable heterogeneity in all analyses, we considered potential moderators that might explain, in part at least, the evident heterogeneity. Both moderators were anticipated a priori (see Sarma et al, 2022). The first was data source.…”
Section: Resultsmentioning
confidence: 99%
“…During the full‐text review process we identified a number of studies that shared the same datasets and, thus, raised concern in relation to the independence of the samples for the data synthesis. Where datasets are shared, we made decisions as to which studies to include in the data synthesis, with all studies being included in the narrative synthesis (see Sarma et al, 2022). Studies were flagged if: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the investigation of the 'terrorist person' a potential mental trouble is almost always among the aspects of study. No wonder that in recent times several studies have been conducted for the very purpose to discover the importance of mental health in terror activity (Sarma-Carthy-Cox 2022).…”
Section: Introductionmentioning
confidence: 99%